Characterisation and implementation of the ERE-CALUX bioassay on indoor dust samples of kindergartens to assess estrogenic potencies. Issue 155 (January 2016) - Vandermarken, T.; De Galan, S.; Croes, K.; Van Langenhove, K.; Vercammen, J.; Sanctorum, H.; Denison, M.S.; Goeyens, L.; Elskens, M.; Baeyens, W.
Highlights: We characterised the ERE-CALUX bioassay and used the 4 parameter Hill equation. We collected dust in 12 different kindergartens classes in Flanders and Brussels. The interior score and the BEQ, or estrogenic activity, showed a good relationship. Increasing amounts of phthalates lead to an increase in BEQ. Abstract: Estrogen-like endocrine disrupting chemicals (EEDCs) can be found abundantly in the environment. Due to their low-dose effects and the large amount of unknown EEDCs, it is difficult to assess and manage possible human health risks. For young children, who are particularly vulnerable to endocrine disruption due to their development rate, indoor dust is one of the main routes of exposure. In this study, an estrogen responsive elements chemically activated luciferase gene expression (ERE-CALUX) bioassay was characterized and implemented for the analysis of 12 dust samples from kindergartens in Flanders and Brussels (Belgium). The human ovarian carcinoma BG 1CALUX cell line showed reproducible results and a low limit of detection (LOD). The effective concentration at 50% of the maximum response (EC50 ) yielded 497 fg/well, while the LOD was 16 fg/well. For all dust samples, full dose–response curves and their corresponding EC50 values could be calculated. All samples yielded bio-analytical equivalent concentrations (BEQs) that were significantly higher than the procedural blank level and ranged from 426 to 8710 pg E2 equivalents/g dust. A clear relationship was observed between a semi-quantitative interior score and the ERE-CALUX response of the samples. In addition, the concentration of phthalates, a major group of EEDCs used as plasticizers in plastics, was determined in the samples by GC–MS. Diisoheptyl phthalate (DiHP) and di(2-ethylhexyl) phthalate (DEHP) were present in every dust sample. A good correlation was found between ERE-CALUX activities and phthalate concentrations, when all phthalates except diisononyl phthalate (DiNP) and diisodecyl phthalate (DiDP), which do not bind to the estrogen receptor, were taken into account. This shows that the ERE-CALUX can provide relevant results concerning exposure to EEDCs from indoor dust. This article is part of a Special Issue entitled 'Endocrine disruptors & steroids'.